RIVER FLOOD HAZARD MODELING: FORECASTING FLOOD HAZARD FOR DISASTER RISK REDUCTION PLANNING - Mohammed, Murphy Ponce (Salehan Institute of Higher Education, 2019)
The objective of the study is to create a flood hazard model of Tarlac River and to calibrate the model based on data gathered from the Philippine Atmospheric Geophysical and Astronomical Services Administration. The study employed analytical method wherein the 1D flood modeling was utilized. GIS, DEM data, rainfall data, river analysis system, HEC-GeoRAS, hydrologic modeling system, and HEC-GeoHMS were utilized. The different flood models revealed that Tarlac River is not expected to be overtopped by flood water as regards the different extreme rainfall events considered in the present study. The RAS model simulation was based on the concept that there is no base flow observed within the river reach before the occurrence of any extreme rainfall event. Henceforth, there is still no 100 percent assurance that the river reach will not be overtopped with the occurrence of initial base flow in combination with the occurrence of higher extreme rainfall events. Further studies or investigations should be delved into such combination of events. Possible levee breach of the Tarlac River as well as the possible incorporation of flood mitigating interventions in future modeling scenarios can be likewise considered.